광촉매 성능 강화를 위한 미세유체공정 기반 Ag-ZnO 나노복합체 합성 - 고재락(Jae-Rak Ko); 전호영(Ho Young Jun); 최창호(Chang-Ho Choi) (Clean Technology, 27(4), 2021)
Recently, there has been increasing demand for advancing photocatalytic techniques that are capable of the efficient removal of organic pollutants in water. TiO2, a representative photocatalytic material, has been commonly used as an effective photocatalyst, but it is rather expensive and an alternative is required that will fulfill the requirements of both high performing photocatalytic activities and cost-effectiveness. In this work, ZnO, which is more cost effective than TiO2, was synthesized by using a microreactor-assisted nanomaterials (MAN) process. The process enabled a continuous production of ZnO nanoparticles (NPs) with a flower-like structure with high uniformity. In order to resolve the limited light absorption of ZnO arising from its large band gap, Ag NPs were uniformly decorated on the flower-like ZnO surface by using the MAN process. The plasmonic effect of Ag NPs led to a broadening of the absorption range toward visible wavelengths. Ag NPs also helped inhibit the electron-hole recombination by drawing electrons generated from the light absorption of the flower-like ZnO NPs. As a result, the Ag-ZnO nanocomposites showed improved photocatalytic activities compared with the flower-like ZnO NPs. The photocatalytic activities were evaluated through the degradation of methylene blue (MB) solution. Scanning electron microscopy (SEM), x-ray diffraction (XRD), and energy-dispersive x-ray spectroscopy (EDS) confirmed the successful synthesis of Ag-ZnO nanocomposites with high uniformity. Ag-ZnO nanocomposites synthesized via the MAN process offer the potential for cost-effective and scalable production of next-generation photocatalytic materials. 물에 잔존하는 유기오염물질이 인체 및 환경에 미치는 악영향을 해결하기 위한 방법으로 오염물질을 친환경적으로 분해할 수 있는 광촉매 기술이 대두되고 있다. 대표적인 광촉매 물질로 TiO2 입자가 사용되고 있지만 비싼 가격으로 인해 이를 대체하고자 하는 노력이 지속적으로 수행되었다. 본 연구에서는 이러한 노력의 일환으로 미세유체공정을 사용하여 보다 가격경쟁력이 우수한 ZnO입자를 합성하였다. ZnO의 넓은 밴드갭으로 인해 촉매활성이 제한되는 단점을 해결하고자 동일 공정을 사용하여 은(Ag) 나노입자를 ZnO 표면에 증착하여 Ag-ZnO 나노복합체를 생산하였다. 다양한 분석법을 사용하여 나노복합체의 형상, 구조, 및 성분 분석을 진행한 결과 고품질의 Ag-ZnO 나노복합체가 합성됨을 확인했으며, 메틸렌블루 분해 실험을 통해서 광촉매 활성을 측정하였다. Ag-ZnO 나노복합체의 플라스몬 효과와 광반응에 의해 생성된 전자와 정공의 분리 효과에 의해 광촉매 활성 효율이 순수한 ZnO 입자와 비교하여 향상되었음을 확인하였다. Microreactor-assisted nanomaterials (MAN) 공정 기반의 나노복합체는 가격경쟁력이 우수하고 공정이 용이하다는 장점이 있기에 나노복합체 광촉매를 대량 생산하기 위한 잠재력이 우수하다고 사료된다.